Spectroscopic observations of the cluster IC 2391 - Feinstein, Alejandro (1961)
With the grating spectrograph of the Bosque Alegre telescope, which gives a dispersion of 42 A/mm, the brightest stars of the galactic cluster IC 2391 were taken,for the purpose of radial velocity measurements and for a provisional spectral classification in the MK system.